Knowing the nature of the “individual”. A proposal from José Ortega y Gasset and Boris Pasternak - Avellaneda Vásquez, Jainor (2023)
Based on the anthropological theory of José Ortega y Gasset and the narrative of Boris Pasternak, this research, with a qualitative approach and grounded theory design, seeks to understand the nature of the individual as an apparent subject of individual rights. To do this, we start from Ortega, arguing that radi- cal reality, our life, my life or each person’s life, situated as a link between the self and the circumstance, gives the ultimate specification to the individual, which is visible in the individual. radical, a human being uprooted from the collective, absolutely identified as what he is (I) and incapable of being absorbed by the world and the events of history (circumstance). Thus, analyzing Pasternak’s novel, Doctor Zhivago, a reading of the nature of the individual at a practical level is proposed through the character Yuri Zhivago, who, as a radical individual, points out his main challenges and contexts in which he develops his life, and then ends by exposing the permanent violation of his individual rights, because his nature (being as he is) collides with the political and social order that a system of government imposes.